Individual and community-level impact of infertility-related stigma in Malawi. (April 2020) - Bornstein, Marta; Gipson, Jessica D.; Failing, Gates; Banda, Venson; Norris, Alison
Abstract: Infertility, a common experience among women and men worldwide, remains on the margins of public health and medicine in low-resource settings. Previous studies identified associations between individual experiences of infertility and negative outcomes, particularly in contexts where childbearing is imperative, but few have examined broader implications of infertility and infertility-related stigma on communities. To understand the production and impact of infertility-related stigma, this study analyzes 12 focus group discussions (FGDs) conducted with 104 women and men in rural Malawi. FGDs, conducted July–September 2018, were used to elicit the range of community norms around family formation, pregnancy, fertility, and infertility. Data were analyzed through memo-ing during and after data collection and collaborative, thematic coding. We found that stigma manifested within existing systems of gender and power. Aligning with Link and Phelan's stigma framework (2001) there were three primary mechanisms by which infertility-related stigma was produced and reinforced: labeling of a person perceived to be infertile (i.e., establishing 'other'), perpetuating negative stereotypes associated with suspected causes of infertility (e.g., abortion, multiple sexual partners, weak sperm), and consequences of infertility that reinforced stigma (e.g., social ridicule and distancing, divorce). Labels, presumed causes, and consequences of infertility were entrenched within gender and sexuality norms. Women perceived as infertile were unable to follow a normative path to achieving adult status, presumed to be sexually transgressive, and considered "useless." Men's masculinity was questioned. Both women's and men's identities, as well as social positions within relationships and communities, were threatened by perceptions of infertility. Ultimately, the manifestation of infertility-related stigma contributed to an environment wherein the risk of being perceived as infertile was highly consequential and unrelenting. Pervasive stigma, at the community-level, impacts decisions around contraceptive use and timing of childbearing, as women and men not only wanted to avoid infertility, but also the appearance of infertility. Highlights: Uses stigma framework to examine community production of infertility-related stigma. Includes women and men, highlighting gendered aspects of infertility-related stigma. Finds both women and men experience stigma, but consequences manifest differently. To alleviate stigma, community-level and gender-specific interventions are needed. Stigma impacts sexual behaviors/decisions broadly, even of those without infertility.